Exploring the potentials of selected bioactive compounds isolated from Piper guineense Schumach. & Thonn. leaf toward identification of novel pfDHFR and pfDHODH inhibitors as antimalaria agents - Oluwafemi Adeleke Ojo (Journal of Applied Pharmaceutical Science, 2021)
Present antimalarial drugs have been related to several adverse side effects, including headache, depression, nausea, and itchy skin. Thus, exploring bioactive compounds from a natural origin, which possess drug-like properties with no side effects, is of great importance. This study was designed to assess the molecular relations obtainable between piperine, pipercide, and piperlongumine compounds isolated from Piper guineense Schumach. & Thonn. leaf and targeted receptor linked to malaria Plasmodium falciparum dihydrofolate reductase (pfDHFR) and Plasmodium falciparum dihydroorotate dehydrogenase (pfDHODH) for antimalarial properties. The result showed that piperine (−8.3 kcal/mol) from P. guineense binds to pfDHFR with high affinity and low free energy than the other compounds and standard ligand pyrimethamine (−7.8 kcal/mol). In contrast, pyrimethamine (−8.4 kcal/mol) and pipercide (−8.3 kcal/mol) show a better binding affinity to pfDHODH. Hence, the results provided insights into the development of better piperine and pipercide as a replacement to present antimalarial agents, with further analysis worth considering.
Keywords: Piper guineense, molecular docking, pfDHFR, pfDHODH, rule of five, toxicity.